Определение параметров импульсной последовательности для адаптивного способа измерения вольт-амперных характеристик полупроводниковых приборов - Ермоленко, Е.А.; Бондаренко, А.Ф.; Баранов, А.Н. (Технічна електродинаміка, 2012)
To implement the adaptive pulse method for measuring the current-voltage characteristics of semiconductor devices the mathematical relation between the duration of pauses that follow the measuring pulses and the power and duration of these pulses is obtained. The use of obtained mathematical formula for specifying parameters of pulse sequence allows to reduce the accumulation of heat in the structure of semiconductor device during the process of measuring the current-voltage characteristics, thereby improving measuring accuracy.